Review and Critique of "Physical Education in Schools" - Mohsen Hallaji (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this research was to review and critique the book “Physical Education in Schools”. For this purpose, the questionnaire "Review and review of texts and books of humanities (national books)" developed by the Institute of Humanities and Cultural Studies as a tool and framework of critique was used. The face, structure, and content validity of the questionnaire were determined by a panel of faculty members inside and outside the Institute of Humanities and Cultural Studies. The book "Physical Education in Schools" has 441 pages of four sections and fifteen chapters. The findings of the critique were presented from two perspectives: points and defects of form and content. Form factors (formal comprehensiveness) were evaluated to the optimum level. Content scores include: the content of sections and chapters to create logical order,internal consistency of content within the seasons, the inclusion of resources at the end of each section, the absence of scientific bias, the proportional of the content with Islamic culture and values, the symmetry of the chapters to be aligned with headings, the use of components of formal comprehensiveness in the transfer of content concepts, the quality of the application, and the equivalence of technical terms. The formal defects are mainly due to the low attractiveness of the cover, the ambiguous expression of the main purpose of the effect, the lack of a preface, a glossary, the goals of the lesson, the summary of the chapter and section, the conclusions and suggestions, the subject glossary, and medium quality printing, including items such as paper type, book cover, set up tables and charts, etc.). Content deficiencies include lack of general idea and disturbance in the use of structural and content models in providing the content of the book, lack of adequate references and incompleteness of them, lack of presenting comprehensive image of all components of the physical education course, relative disregard referring to the existing scientific theories, the discrepancy between the content of the book and the heading of a particular lesson, and finally the failure to use all the components of formal comprehensiveness in the conveying and strengthening of the content.